Health care system hazard vulnerability analysis: an assessment of all public hospitals in Abu Dhabi. Issue 2 (April 2014) - Fares, Saleh; Femino, Meg; Sayah, Assaad; Weiner, Debra L.; Yim, Eugene Sun; Douthwright, Sheila; Molloy, Michael Sean; Irfan, Furqan B.; Karkoukli, Mohamed Ali; Lipton, Robert; Burstein, Jonathan L.; Mazrouei, Mariam Al; et al.
<x xml:space="preserve">Abstract</x> Hazard vulnerability analysis (HVA) is used to risk‐stratify potential threats, measure the probability of those threats, and guide disaster preparedness. The primary objective of this project was to analyse the level of disaster preparedness in public hospitals in the Emirate of Abu Dhabi, utilising the HVA tool in collaboration with the Disaster Medicine Section at Harvard Medical School. The secondary objective was to review each facility's disaster plan and make recommendations based on the HVA findings. Based on the review, this article makes eight observations, including on the need for more accurate data; better hazard assessment capabilities; enhanced decontamination capacities; and the development of hospital‐specific emergency management programmes, a hospital incident command system, and a centralised, dedicated regional disaster coordination centre. With this project, HVAs were conducted successfully for the first time in health care facilities in Abu Dhabi. This study thus serves as another successful example of multidisciplinary emergency preparedness processes.